Efficacy of telbivudine with conditional tenofovir intensification in patients with chronic hepatitis B: results from the 2-year roadmap strategy - Teerha Piratvisuth; Piyawat Komolmit; Henry LY Chan; Tawesak Tanwandee; Wattana Sukeepaisarnjaroen; Mário G Pessoa; Eduardo Fassio; Suzane K Ono; Fernando Bessone; Jorge Daruich; Stefan Zeuzem; Michael Manns; et al. (BioExcel Publishing Ltd, 2016)
Background: A 2-year roadmap study was conducted to evaluate the efficacy and safety of tenofovir intensification at Week 24 in patients with chronic hepatitis B (CHB) receiving telbivudine. Scope: A prospective multicenter study was conducted in treatment-naive patients with hepatitis B e antigen (HBeAg)- positive CHB. All patients received telbivudine (600 mg/day) until Week 24. Thereafter, patients with detectable hepatitis B virus (HBV) DNA (≥300 copies/mL) were administered tenofovir (300 mg/day) plus telbivudine, and patients with undetectable HBV DNA continued telbivudine monotherapy until Week 104. The primary endpoint was the proportion of patients with undetectable HBV DNA (<300 copies/mL) at Weeks 52 and 104. Findings: A total of 105 patients were enrolled in the trial, of which 100 were eligible for efficacy analysis. Undetectable HBV DNA levels were observed at Week 24 in 55 patients who continued on with telbivudine monotherapy. The remaining 45 patients with detectable HBV DNA received tenofovir add-on therapy. With monotherapy, 100% (55/55) and 94.5% (52/55) of patients achieved HBV DNA <300 copies/mL at Weeks 52 and 104, respectively; the corresponding values for patients with add-on therapy were 84.4% (38/45) and 93.3% (42/45). Overall, undetectable HBV DNA (<300 copies/mL) was found in 93% (93/100) and 94% (94/100) of patients at Weeks 52 and 104, respectively. HBeAg seroconversion rate was 44.4% (44/99) at Week 104 for the overall patient population. One patient in the monotherapy group and six in the intensification group demonstrated HBsAg clearance at Week 104. HBsAg seroconversion was observed in four patients at Week 104, all belonged to the tenofovir intensification group. Eight patients sustained HBsAg loss during a posttreatment follow-up period of 16 weeks. Alanine aminotransferase (ALT) normalization was constant in the telbivudine monotherapy group, whereas a progressive improvement was observed in the tenofovir intensification group. Two patients in the monotherapy and none in the intensification group experienced viral breakthrough by Week 104. There were no reports of myopathy in either group. The mean changes in estimated glomerular filtration rate (eGFR), estimated using the Modification of Diet in Renal Disease (MDRD) formula, from baseline to Week 104 were +6.145 mL/min/1.73 m2 (p=0.0230) and +7.954 mL/min/1.73 m2 (p=0.0154) in the telbivudine monotherapy and tenofovir intensification groups, respectively. The incidence of serious AEs was four in the telbivudine monotherapy and two in the tenofovir intensification group. The main limitation of this study was limited sample size, which made the power of the observation low, and the absence of a comparative subgroup to assess the progression of patients with detectable HBV DNA without treatment intensification. Conclusions: Data from this 2-year roadmap study confirmed that telbivudine with add-on tenofovir was effective and well tolerated in patients with CHB. Telbivudine was associated with an improvement in eGFR from baseline in both the groups.